2022
DOI: 10.3389/fonc.2022.986305
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of growth hormone receptor signaling by using pegvisomant: A functional therapeutic strategy in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is an aggressive neoplasm with poor clinical outcome because most patients present at an advanced stage, at which point curative surgical options, such as tumor excision or liver transplantation, are not feasible. Therefore, the majority of HCC patients require systemic therapy. Nonetheless, the currently approved systemic therapies have limited effects, particularly in patients with advanced and resistant disease. Hence, there is a critical need to identify new molecular targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Despite this recent breakthrough in the treatment of patients with advanced HCC, there remains an unmet need for reliable biomarkers of response to immunotherapy.GH level have been reported and validated as a prognostic marker in HCC patients [ 7 , 12 , 13 ]. Our group reported in previous studies the prognostic value of circulating GH level in all 767 patients with different disease stages and treatment modalities received and also compared them to healthy volunteers (200 cases) [ 2 , 13 ]. Our group also recently reported a significant correlation between GH level and overall survival [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this recent breakthrough in the treatment of patients with advanced HCC, there remains an unmet need for reliable biomarkers of response to immunotherapy.GH level have been reported and validated as a prognostic marker in HCC patients [ 7 , 12 , 13 ]. Our group reported in previous studies the prognostic value of circulating GH level in all 767 patients with different disease stages and treatment modalities received and also compared them to healthy volunteers (200 cases) [ 2 , 13 ]. Our group also recently reported a significant correlation between GH level and overall survival [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it provides the basis to investigate the potential integration of anti-GH strategies, such as pegvisomant; a short peptide that inhibits the GH/GHR signaling and is the only drug approved by FDA to treat acromegaly [ 14 ], into systemic therapy approaches in HCC. Our group recently reported that GHR signaling could be a potential successful target in HCC [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pegvisomant (also referred to as Somavert) is an FDA-approved prescription medicine used for acromegaly patients and functions as a GHR antagonist to block GH/GHR signaling [56]. HCC cell lines, such as HepG2 cells, express higher levels of GHR compared to normal human liver cells, and pegvisomant treatment inhibited HCC tumor growth and increased sensitivity against sorafenib in HepG2 xenograft mouse models [55]. These findings indicate that abnormally elevated GH signaling may contribute to hepatic tumorigenesis and HCC…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The majority of Ghr +/+ (93.5%) and Ghr +/-(87.1%) mice showed HCC development after DEN treatments, but 5.6% of Ghr -/mice developed HCC, indicating the vital roles of GH signaling in hepatic tumorigenesis and the therapeutic potentials of targeting GHR [54]. Kaseb et al analyzed plasma samples of 767 HCC patients and demonstrated that patients with high GH levels suffered more frequent cirrhosis, higher α-fetoprotein (AFP) levels, more advanced stages, and lower overall survival compared to patients with low GH plasma levels [55]. Interestingly, patients with high GH levels showed significantly lower circulating IGF1 levels than low GH patients [55].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation